Dynamics of splashed droplets impacting wheat leaves treated with a fungicide. Issue 168 (29th July 2020) - Park, Hyunggon; Kim, Seungho; Gruszewski, Hope A.; Schmale, David G.; Boreyko, Jonathan B.; Jung, Sunghwan
Abstract : Wheat is threatened by diseases such as leaf rust. One significant mechanism of disease spread is the liberation and dispersal of rust spores due to rainsplash. However, it is unclear to what extent the spore-laden splashed droplets can transmit the disease to neighbouring leaves. Here, we show that splashed droplets either bounce or stick, depending on the orientation of the leaf and whether the surface of the leaf has been treated with a fungicide. A scaling model revealed that bouncing was enabled when the droplet's kinetic energy exceeded its pinning energy to the surface. Our findings indicate that, ironically, the application of fungicide to protect a wheat plant may also facilitate pathogen spread and infection by making leaves sticky to spore-laden droplets.